One-dimensional acoustic diodes based on the anisotropy of solid media and linear acoustics. (March 2015) - Chen, Shi; Hao, Changchun; Wang, Chenghui; Zhang, Yinhong; Lin, Shuyu
Abstracts: Existing acoustic diodes are solid–liquid systems and do not involve the inherent anisotropy of solid media. They are based on either the nonlinear effect or the diffraction effect. A kind of new acoustic diodes is proposed in this paper. These new acoustic diodes are all solid medium systems. They are based on the anisotropy of solid media and complete linear acoustics. Compared with the acoustic diodes based on the nonlinear effect, these acoustic diodes proposed here own higher transmission in their forward direction.